Clinical and Morphological Features of Paraduodenal Pancreatitis: An Italian Experience With 120 Patients. Issue 4 (April 2017) - de Pretis, Nicolò; Capuano, Fabiana; Amodio, Antonio; Pellicciari, Mattia; Casetti, Luca; Manfredi, Riccardo; Zamboni, Giuseppe; Capelli, Paola; Negrelli, Riccardo; Campagnola, Pietro; Fuini, Arnaldo; Gabbrielli, Armando; et al.
Abstract : Objectives: This study aimed to evaluate the clinical and radiological features and clinical outcomes of paraduodenal pancreatitis (PP). Methods: A final diagnosis of PP was based on surgical specimens in resected patients and on imaging in nonoperated patients. Clinical, radiological, and pathological data were collected and reevaluated. Results: We studied 120 patients, 97.5% of whom were drinkers and 97.5% were smokers. Symptoms at clinical onset were acute pancreatitis in 78 patients (65%) and continuous pain in 68 patients (55.8%). Other symptoms were vomiting (36.7%), weight loss (25.8%), and jaundice (11.7%). Cystic variant was diagnosed in 82 patients (68.0%), and solid variant was diagnosed in 38 patients (32.0%). Pure and diffuse forms were observed in 22 (18.3%) and 98 (81.7%) patients, respectively. Pancreatic calcifications were present at clinical onset in 5.0% of the patients and in 61.0% at the end of follow-up. Somatostatin analogs were used in 13 patients (10.8%), and 81 patients (67.0%) underwent surgery. Conclusions: The clinical profile of PP was found to be middle-aged men who were heavy drinkers and smokers with painful pancreatitis and was associated with vomiting and weight loss. In nonresponders, alcohol withdrawal and medical therapy can be proposed as a first-line treatment, and surgery as a second-line treatment.